UJI AKTIVITAS EKSTRAK ETANOL DAUN KEJIBELING (Strobilanthes crispus Linn) TERHADAPA PENURUNAN KADAR GLUKOSA DARAH PADA MENCIT JANTAN (Mus musculus) - Faridha Yenny Nonci; Dwi Wahyuni Leboe; Armaila Armaila (Jurnal Farmasi UIN Alauddin Makassar, 2016)
Have been conducted a research examining the effect of ethanol extract of leaves kejibeling (Strobilanthes Crispus Linn) to degrade blood glucose level to male mice (Mus musculus). This aim of this research to find out the effect and to decide concentration of ethanol extract of leaves kejibeling can be used to degradation blood glucose level to male mice which induce by glucose 20 %. This research uses 15 male mice which devide by 5 group in treatment, where each experiment consist of 3 tail. Group of I was given Na CMC 1 % as negative control, group II, III, and IV were given of ethanol extract of leaves kejibeling with concentration 7,35 mg/ g BW, 14,7 mg/ g BW and 29,4 mg/ g BW and group V was given metformin 1,95 mg/ g BB mice as positive control. The result of the research was examined statistically by using method Group Random Design and continued Duncan test showed that effect of ethanol extract of leaves kejibeling with concentration 14,7 mg/ g BB do not differ reality was given metformin 1,95 mg/ g BB male mice, can degrade the rate of blood glucose.